A Transitional Text Reflecting Characteristics of Old Anatolian Turkish and Ottoman Turkish: İblis Nasihati - Karaca, Hasan (Fırat University, 2025)
İblis Nasihati narrates a dialogue in the form of questions and answers, reportedly taking place between the Prophet Muhammad and Iblis. The story originates from a hadith narrated by Ibn Abbas. According to this account, Allah commands Iblis to attend the Prophet Muhammad's assembly and respond correctly to the questions posed to him. The Prophet asks 52 questions, mainly regarding the individuals, acts of worship, and behaviors that Iblis either favors or despises. The focus of this study is the work titled İblis Nasihati, which is the first of five texts compiled within a single manuscript consisting of 98 folios. It is cataloged in the Manuscripts Collection of the National Library under the reference 06 Mil Yz A 3907/1. The text is written in vocalized naskh script, with each page containing 15 lines and a total of 10 folios. However, the manuscript does not include information about the date of composition, the author, or the scribe. Linguistically, the text exhibits features of both Old Anatolian Turkish and 17th- and 18th-century Ottoman Turkish. In this study, the manuscript is transcribed, analyzed in terms of its genre, writing style, and linguistic features, and presented in detail.

İblis Nasihati, Hz. Muhammed ile İblis arasında gerçekleştiği rivayet edilen soru ve cevaba dayalı görüşmeyi anlatır. Hikâyenin kaynağı İbn Abbas’dan rivayet edilen bir hadistir. Buna göre Allah, Hz. Muhammed’in meclisine sorulacaklara doğru cevap vermesi emriyle İblis’i gönderir. Hz. Muhammed, genel olarak İblis’in sevip sevmediği kişi, ibadet ve davranışlarla ilgili 52 soru sorar. Soru ve cevaplar Müslümanlara doğru ve yanlışı gösterecek niteliktedir. Türk edebiyatında değişik adlarla bu kıssayı anlatan yazma metinler vardır. Bunların bir kısmı müstakil eser şeklinde olup bir kısmı da mecmualar bünyesindedir. Bu çalışmaya konu olan İblis Nasihati beş eserden oluşan ve tek kalemden çıkmış 98 varaklık bir mecmuanın ilk eseridir. Yazma, Millî Kütüphane Yazmalar Koleksiyonu’nda 06 Mil Yz A 3907/1 katalog bilgisiyle kayıtlıdır. Harekeli nesihle yazılmıştır. Eserin içerik veya katalog kaydında herhangi bir yazılış tarihi, müellif veya müstensih bilgisi yoktur. Metin, hem Eski Anadolu Türkçesi hem 17 ve 18. yüzyıl Osmanlı Türkçesi özelliklerini barındırmaktadır. Bu çalışmada söz konusu yazmanın metni transkribe edilmiş, tür, yazım ve dil özellikleriyle değerlendirilip tanıtılmıştır.
Eski Anadolu Türkçesi ve Osmanlı Türkçesi Özellikleri Taşıyan Bir Geçiş Dönemi Metni: İblis Nasihati
Keywords: Linguistic Structures (Incl. Phonology; Morphology and Syntax); Dilsel Yapılar (Fonoloji; Morfoloji ve Sözdizimi dahil)